Comparing between virtual reality based pre-clinical implantation training and traditional learning methods - Li, Yangjie; Chen, Xu; Huang, Yuan ding; He, Qingqing; Li, Dize; Hu, Shanshan; Xu, Peng; Chen, Tao; Ran, Xiongwen (PeerJ, 2025)
Objective As dental implanting becomes an increasing demand among patients with tooth loss, an efficient and effective training for students is to be necessary. In this case, we anticipate the possible application of virtual reality (VR) technology to pre-clinical implantation training (PCIT) in order to improve the students’ learning efficiency and effectiveness. Methods The study divided 20 subjects into two groups on average—VR based PCIT (experimental group) and traditional PCIT (control group) with the completion of the background survey (BS) before PCITs, to guarantee no apparent backgroud variation including learning of oral implantology and VR technology, learning habits, interests and hobbies, etc. All subjects received identical professional tests (T-1, T-2, T-3) before, in and after PCITs to assess the knowledge mastery condition and maintaining levels. Along with both PCITs, the subjective evaluation tests (SET) were distributed to collect the subjective feedback data so as to analyze the preference to each PCIT. Meanwhile the total interaction time, learning duration per subject were recorded for the performance analysis. Results The results show that from T-1 to T-2 period, the score of VR based PCIT increased significantly (p < 0.05). And the results of SET show that subjects in VR based PCIT generally obtain over one score higher than the ones in traditional PCIT as for the items of “Convenience”, “Interest”, “Comfort”, “Confidence” and “Subjective initiative” except “Precision”. During both PCITs, VR based PCIT shows a shorter learning duration and sufficient one-on-one interaction opportunities. Conclusion Compared with traditional PCIT, VR based PCIT has obvious influence on enhancing students’ knowledge mastery, study willingness and learning efficiency.
Keywords: VR based PCIT; Virtual reality; Implantation training